Central retinal vein occlusion in the setting of fibroblast growth factor receptor inhibition - William Foulsham; Benjeil Z. Edghill; O.D. Julia Canestraro; Vicky Makker; Jason Konner; David H. Abramson; Jasmine H. Francis (American Journal of Ophthalmology Case Reports, 2022)
Purpose: To report a case of central retinal vein occlusion (CRVO) in a patient being treated with a fibroblast growth factor receptor (FGFR) inhibitor. Observations: A 54-year-old female patient with endometrial cancer presented with CRVO and cystoid macular edema while receiving lenvatinib/pembrolizumab combination therapy. The patient received treatment with intravitreal bevacizumab, after which her visual acuity improved markedly, permitting the continuation of her chemotherapy regimen without recurrence of ocular adverse events. Conclusions and Importance: Like mitogen-activated protein kinase inhibitors, FGFR inhibitors have the potential to be associated with retinal vein occlusion. In this case, visual recovery was possible with intravitreal anti-vascular endothelial growth factor therapy, and toxicity did not recur with drug reinitiation and continuation over five years of follow-up.